Fabrication and Evaluation of Mechanical Properties of Fe2O3 Particulate Filled Hybrid Composites - Chavan, Vithal Rao; Dinesh, K. R.; Veeresh, K.; Reddy, G. Jagannatha; Algur, Veerabhadrappa; Venkatesh (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
The researchers are quite concentrating at the hybrid materials. this is mainly due to their applicable benefits have they offer low density, low cost,etc., an experimental investigation was conducted to study the effect of hematite ore and volume fraction on Tensile Strength, Hardness, Impact Strength of Hybrid composite. General Purpose resin or Orthophthalic resin, E-Glass fiber, and Hematite ore are the constitute of hybrid composite. Specimen was cut from the fabricated laminate according to the ASTM standard for different experiments for tensile test, hardness test, and impact test. The laminates are prepared by varying the volume fraction (6%, 8%, 10 %,). The results shown that the incorporation of hematite ore has a strong influence on the properties.